EdTech-Based Gamification Integration in the Development of Multimodal Literacy for Madrasah Ibtidaiyah Students - Faizatul Widat; Baharun, Hasan; Abdul Wahid Zaini; Ombra A. Imam (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study investigates the integration of educational technology-based gamification (EdTech) in fostering the multimodal literacy of madrasah ibtidaiyah students. The researchers employed a qualitative case study design and conducted the study at MI Darul Lughah Wal Karomah through classroom observations, in-depth interviews, and document analysis. The study examines how teachers design multimodal gamification activities using platforms such as Wordwall, Quizizz, and Kahoot; how multimodal literacy practices emerge; and how students respond to interactive digital learning content. The findings reveal that teachers strategically integrate visual, audio, and textual elements into gamified tasks to promote cross-modal understanding. Students demonstrated multimodal literacy through their interactions with visual and auditory content on EdTech platforms, which stimulated multisensory learning. They also showed greater engagement, faster reading, and improved ability to interpret meaning across different modes of representation. These results indicate that gamification functions not only as an instructional tool but also as a strategic medium for cultivating 21st-century literacy competencies. This study provides practical insights for designing contextualized multimodal learning strategies in madrasas and contributes to the broader discourse on digital literacy in Islamic-based elementary education.